Between Legal Fortress and Uncertainty: Comparative Analysis of the Refugee Law Frameworks in Hungary and Indonesia - Bahri, Mohammad Thoriq (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
This study compares the legal frameworks of Hungary and Indonesia in dealing with the massive influx of refugees in their respective countries. While Hungary has successfully reduced the number of asylum seekers through a "fortress" approach using its Asylum Act of 2007, Indonesia’s legal framework, as seen in Presidential Regulation 125/2016, lacks the procedures for converting asylum seekers into refugees. This is compounded by the absence of a refugee status determination process in Indonesia, making it challenging to provide assistance to increasing numbers of asylum seekers entering the country yearly. To address this problem, Indonesia must first make national legal changes that reflect its sociopolitical realities before ratifying the 1951 Refugee Convention and the 1967 Protocols. In contrast, Hungary’s legal framework, while effective in reducing the number of asylum seekers, has been criticized for being restrictive and failing to respect human rights.